Resistance development and insecticide susceptibility in Culex quinquefasciatus against selection pressure of malathion and permethrin and its relationship to cross-resistance towards propoxur. - Selvi, S.; Endah, M.A.; Nazni, W.A.; Lee, H.L.; Azahari, A.H. (2005)

(untitled)
To determine resistance level and characterize malathion and permethrin resistance in Culex quinquefasciatus, two methods were used namely: WHO procedures of larval bioassay to determine the susceptibility of lethal concentration (LC) and adult bioassay to determine the lethal time (LT) which are resistant to malathion and permethrin. These mosquito strains were bred in the Insectarium, Division of Medical Entomology, IMR. Thousands of late fourth instar larvae which survived the selection pressure to yield 50% mortality of malathion and permethrin were reared and colonies were established from adults that emerged. Larvae from these colonies were then subjected to the subsequent 10 generations in the test undertaken for malathion resistant strain (F61 - F70) and permethrin resistant strain (F54 - F63). Selection pressure at 50% - 70% mortality level was applied to the larvae of each successive generation. The rate of resistance development and resistance ratio (RR) were calculated by LC5 0 for larval bioassay and LT50 value for adult bioassay. The lab bred Cx. quinquefasciatus was used as a susceptible strain for comparison purpose. The adult bioassay test was carried out by using diagnostic dosages of malathion 5.0%, permethrin 0.75% and with propoxur 0.1%. All bioassay results were subjected to probit analysis. The results showed that LC5 0 for both malathion (F61 - F70) and permethrin (F54 - F63) resistant Cx. quinquefasciatus increased steadily to the subsequent 10 generations indicating a marked development of resistance. The adult female malathion resistant strain have developed high resistance level to malathion diagnostic dosage with resistance ratio 9.3 to 9.6 folds of resistance. Permethrin resistance ratio remained as 1.0 folds of resistance at every generation. It was obvious that malathion resistance developing at a higher rate in adult females compared to permethrin. Female adults exposed to 2 hours of exposure period for propoxur 0.1% showed presence of cross-resistance among the both strains of mosquitoes towards propoxur and it was indicated by 70%-100% mortality at 24 hours post-recovery period.